Pengaruh kepemimpinan instruksional terhadap kualitas pembelajaran guru sekolah dasar - Amelia, Dian Putri; Sulastri; Srihandaryati, Heny; Nurhuda, Galih (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to analyze the level of principals’ instructional leadership, the quality of teachers’ instruction, and to examine the effect of instructional leadership on the quality of teachers’ instruction in elementary schools in Tlogomulyo District. The study employed a quantitative approach with a correlational ex post facto research design. The population consisted of all elementary school teachers in Tlogomulyo District, while the sample was selected using proportional random sampling techniques. Data were collected through questionnaires, observations, and documentation. Data analysis was conducted using prerequisite tests (normality and linearity), simple regression analysis, and t-tests. The findings revealed that the principals’ instructional leadership was categorized as good, with a mean score of 135.96, while the quality of teachers’ instruction was also categorized as good, with a mean score of 167.82. The regression analysis indicated that instructional leadership had a positive and significant effect on the quality of teachers’ instruction, as reflected in the regression equation Ŷ = 56.596 + 0.813X and a significance value of 0.000 < 0.05. The coefficient of determination (R²) showed that instructional leadership contributed 23.5% to the quality of teachers’ instruction. Based on these findings, it can be concluded that principals’ instructional leadership has a significant influence on improving the quality of teachers’ instruction. Therefore, strengthening instructional leadership should be continuously promoted in order to enhance the quality of learning in elementary schools. Abstrak Penelitian ini bertujuan untuk menganalisis tingkat kepemimpinan instruksional kepala sekolah, kualitas pembelajaran guru, serta menguji pengaruh kepemimpinan instruksional terhadap kualitas pembelajaran guru di Sekolah Dasar (SD) Kecamatan Tlogomulyo. Penelitian ini menggunakan pendekatan kuantitatif dengan desain ex post facto yang bersifat korelasional. Populasi penelitian adalah seluruh guru SD di Kecamatan Tlogomulyo, dengan sampel yang diambil menggunakan teknik proportional random sampling. Teknik pengumpulan data menggunakan angket, observasi, dan dokumentasi. Analisis data dilakukan melalui uji prasyarat (normalitas dan linearitas), analisis regresi sederhana, serta uji t. Hasil penelitian menunjukkan bahwa kepemimpinan instruksional kepala sekolah berada pada kategori baik dengan nilai rata-rata 135,96, sedangkan kualitas pembelajaran guru juga berada pada kategori baik dengan nilai rata-rata 167,82. Hasil analisis regresi menunjukkan bahwa kepemimpinan instruksional berpengaruh positif dan signifikan terhadap kualitas pembelajaran guru, dengan persamaan regresi (Y ) ̂= 56,596 + 0,813X dan nilai signifikansi 0,000 < 0,05. Koefisien determinasi sebesar 0,48 menunjukkan bahwa kepemimpinan instruksional memberikan kontribusi sebesar 23,5% terhadap kualitas pembelajaran guru. Berdasarkan hasil penelitian dapat disimpulkan bahwa kepemimpinan instruksional kepala sekolah memiliki pengaruh yang signifikan dalam meningkatkan kualitas pembelajaran guru. Oleh karena itu, penguatan kepemimpinan instruksional perlu dilakukan secara berkelanjutan guna meningkatkan mutu pembelajaran di sekolah dasar.